Oncocytic intraductal carcinoma of salivary glands: a distinct variant with TRIM33–RET fusions and BRAF V600E mutations - Bishop, Justin A (Histopathology, 2021)
AIMS: Salivary gland intraductal carcinoma (IDC) is a complex ductal neoplasm surrounded by a layer of myoepithelial cells. Recent insights have shown that there are three different types: intercalated duct-like, with frequent NCOA4–RET fusions; apocrine, with salivary duct carcinoma-like mutations; and mixed intercalated duct-like/apocrine, with RET fusions, including TRIM27–RET. In addition, an oncocytic IDC has been described, but it remains unclear whether it represents a fourth variant or simply oncocytic metaplasia of another IDC type. Our aim was to more completely characterize oncocytic IDC. METHODS AND RESULTS: Six IDCs with oncocytic changes were retrieved from the authors’ archives, from three men and three women ranging in age from 45 to 75 years (mean, 63 years). Five arose in the parotid gland, with one in an accessory parotid gland. Four patients with follow-up were free of disease after 1–23 months. Several immunostains (S100, mammaglobin, androgen receptor, and p63/p40) and molecular tools (RNA sequencing, RET fluorescence in-situ hybridisation, BRAF V600E VE1 immunohistochemistry, and Sanger sequencing) were applied. Histologically, the tumours were variably cystic with solid intracystic nodules often difficult to recognise as intraductal. In all, tumour ducts were positive for S100 and mammaglobin, negative for androgen receptor, and completely surrounded by myoepithelial cells positive for p63/p40. Molecular analysis revealed TRIM33–RET in two of six cases, NCOA4–RET in one of six cases, and BRAF V600E in two of six cases. One case had no identifiable alterations. CONCLUSIONS: Oncocytic IDC shares similarities with intercalated duct-like IDC. Although additional verification is needed, the oncocytic variant appears to be sufficiently unique to be now regarded as the fourth distinct subtype of IDC. Because of its indolent nature, oncocytic IDC should be distinguished from histological mimics.